Comparison of oncological outcomes in elderly early-stage cervical cancer patients treated with radical surgery or radiotherapy: A real-world retrospective study with propensity score matching - Gu, Yu; Cheng, Hongyan; Cang, Wei; Chen, Lihua; Yang, Junjun; Xiang, Yang (Frontiers in Oncology, 2023)
Objective: To compare the oncological outcomes of radical surgery and radical radiotherapy in elderly (over 65 years) patients with early-stage cervical cancer (IB-IIA). Methods: Elderly patients with stage IB-IIA cervical cancer treated at Peking Union Medical College Hospital from January 2000 to December 2020 were retrospectively reviewed. All patients were divided into the radiotherapy group (RT group) and the operation group (OP group) according to their primary intervention. Propensity score matching (PSM) analysis was performed to balance the biases. The primary outcome was overall survival (OS), and the secondary outcome were progression free survival (PFS) and adverse effects. Results: A total of 116 patients were eligible for the study (47 in the RT group, and 69 in the OP group); and after PSM, 82 patients were suitable for further analysis (37 in the RT group, and 45 in the OP group). In real-world setting, it was found that compared with radiotherapy, operation was more frequently selected for elderly cervical cancer patients with adenocarcinoma(P<0.001) and IB1 stage cancer(P<0.001). The 5-year PFS rates between RT and OP group were not significant (82.3% vs. 73.6%, P=0.659), and the 5-year OS rates of OP group were significantly better than that in RT group (100% vs. 76.3%, P=0.039), especially in patients with squamous cell carcinoma (P=0.029), and tumor size of 2~4cm with G2 differentiation (P=0.046). There was no significant difference in PFS between the two groups(P=0.659). In the multivariate analysis, compared with operation, radical radiotherapy was an independent risk factor of OS (Hazard ratio=4.970, 95% CI,1.023~24.140, P=0.047). No difference was observed in adverse effects between the RT and OP group (P=0.154), and in ≥grade 3 adverse effects (P=0.852). Conclusion: The study found that surgery was more frequently selected for elderly cervical cancer patients with adenocarcinoma and IB1 stage cancer in the real-world setting. After PSM to balance the biases, it showed that compared with radiotherapy, surgery could improve the OS of elderly early-stage cervical cancer patients and was an independent protective factor of OS in elderly early-stage cervical cancer patients.